Prescribing practice of pregabalin/gabapentin in pain therapy: an evaluation of German claim data. Issue 3 (30th March 2019) - Viniol, Annika; Ploner, Tina; Hickstein, Lennart; Haasenritter, Jörg; Klein, Karl Martin; Walker, Jochen; Donner-Banzhoff, Norbert; Becker, Annette
Abstract : Objectives: To analyse the prevalence and incidence of pregabalin and gabapentin (P/G) prescriptions, typical therapeutic uses of P/G with special attention to pain-related diagnoses and discontinuation rates. Design: Secondary data analysis. Setting: Primary and secondary care in Germany. Participants: Four million patients in the years 2009–2015 (anonymous health insurance data). Intervention: None. Primary and secondary outcome measures: P/G prescribing rates, P/G prescribing rates associated with pain therapy, analysis of pain-related diagnoses leading to new P/G prescriptions and the discontinuation rate of P/G. Results: In 2015, 1.6% of insured persons received P/G prescriptions. Among the patients with pain first treated with P/G, as few as 25.7% were diagnosed with a typical neuropathic pain disorder. The remaining 74.3% had either not received a diagnosis of neuropathic pain or showed a neuropathic component that was pathophysiologically conceivable but did not support the prescription of P/G. High discontinuation rates were observed (85%). Among the patients who had discontinued the drug, 61.1% did not receive follow-up prescriptions within 2 years. Conclusion: The results show that P/G is widely prescribed in cases of chronic pain irrespective of neuropathic pain diagnoses. The high discontinuation rate indicates a lack of therapeutic benefits and/or the occurrence of adverse effects.